Strong ion analysis at the bedside. Issue 10 (October 2022) - Loubser, Vera-Lisa; Hughes, Ryan; Brain, Matthew J.
Abstract: Quantitative physicochemical models of human acid-base physiology filled a void between clinical acid-base analysis and general fluid physiology. The physicochemical model is frequently perceived as too complex for bedside use, however a set of simplified screening questions based on Stewart's model can be utilized to aid acid-base interpretation. Emphasis is placed on understanding the acid-base consequences of hypoalbuminaemia, volume status, tonicity and chloride administration as these are common in intensive care unit patients.